2009
DOI: 10.1248/bpb.32.1359
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Salidroside on Endothelial Cell Apoptosis Induced by Cobalt Chloride

Abstract: Salidroside is a major constituent of Rhodiola rosea L. that elicits beneficial effects for ischemic cardiovascular diseases. The aim of this study was to investigate the protective effects of salidroside on endothelial cells apoptosis induced by the hypoxia mimicking agent, cobalt chloride. After challenge with cobalt chloride for 24 h, loss of cell viability and excessive apoptotic cell death were observed in EA.hy926 endothelial cells, and the level of intracellular reactive oxygen species (ROS) increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…The increased formation of ROS is thought to be a key event in the pathogenesis of DR. 17) On the other hand, it is known that both hypoxia and hypoxia-mimicking agents increase ROS generation and activation of several intracellular signaling pathways. 10,18) In this study, CoCl 2 decreased the expression of EC-SOD accompanied with the increase of VEGF, a pro-inflammatory factor. Pre-treatment with NAC significantly suppressed the ROS production, down-regulation of EC-SOD, and up-regulation of VEGF induced by CoCl 2 .…”
Section: Discussionsupporting
confidence: 50%
“…The increased formation of ROS is thought to be a key event in the pathogenesis of DR. 17) On the other hand, it is known that both hypoxia and hypoxia-mimicking agents increase ROS generation and activation of several intracellular signaling pathways. 10,18) In this study, CoCl 2 decreased the expression of EC-SOD accompanied with the increase of VEGF, a pro-inflammatory factor. Pre-treatment with NAC significantly suppressed the ROS production, down-regulation of EC-SOD, and up-regulation of VEGF induced by CoCl 2 .…”
Section: Discussionsupporting
confidence: 50%
“…Unfortunately, the mechanisms underlying these changes have not been clearly delineated, and no suitable drug that can reverse these changes has been identified. According to a research conducted by Tan et al [26], SAL may represent a novel therapeutic agent for the treatment and prevention of hypoxia and oxidative stress-related diseases via targeting HIF-1α, indicating the possible target of SAL in FSGS. HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…1a), has been documented to possess neuroprotective effects against neuronal damage induced by various insults. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, the underlying mechanisms are still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…SA can reduce the degree of cerebral edema and the brain infarct size of rats with global cerebral ischemia, relieve the metabolism abnormity of free radicals and improve the function of cognition as well as behavioral and histological outcomes. [20][21][22] [23][24][25][26][27][28][29][30][31][32][33] In addition, it has been reported that SA may regulate mTOR signaling in cultured human umbilical vein endothelial cells (HUVECs) or in bladder cancer cell lines. 34,35) However, whether the neuroprotective effects of SA involve regulation of the mTOR signaling pathway in PC12 cells is still unknown.…”
mentioning
confidence: 99%